Does Neoadjuvant Chemotherapy for Breast Cancer Affect Lymph Node Harvest Rates?. Issue 7 (July 2019) - White, Richard L.; Palmer, Pooja P.; Trufan, Sally J.; Sarma, Deba
Some authors report that patients receiving neoadjuvant chemotherapy have fewer lymph nodes harvested during axillary dissection and more dissections with < 10 nodes compared with patients who undergo surgery initially. We sought to determine whether there was a difference between these patient groups in terms of number of nodes harvested and number of dissections with < 10 nodes. Retrospective review of 258 patients diagnosed with breast cancer who underwent an axillary lymph node dissection between July 1, 2015, and December 31, 2017 was performed. Chi-squared test was used to assess differences between patient groups. Of 258 patients undergoing dissection, 48 per cent received neoadjuvant chemotherapy; 52 per cent underwent surgery as first therapeutic intervention. Mean number of nodes resected; 14.3 + 6.3 for patients with no prior chemotherapy versus 14.9 + 6.6 for patients with neoadjuvant chemotherapy ( P = 0.48). For patients undergoing surgery as first intervention, 21 per cent had < 10 nodes harvested. For patients receiving neo-adjuvant chemotherapy, 20 per cent had < 10 nodes harvested. Patients who received neoadjuvant chemotherapy showed no statistically significant difference in the number of lymph nodes harvested during axillary dissection compared with patients undergoing surgery as first intervention. Neoadjuvant chemotherapy does not reduce the node harvest at the time of axillary dissection.